The Effectiveness Of Online Learning Activity Through Students’ Speaking Ability At Ibrahimy University - Musdalifah Musdalifah; Raudhatul Islam (MUNAQASYAH : Jurnal Ilmu Pendidikan dan Pembelajaran, 2022)
Online learning activity is one of the most effective lecture methods during the covid-19 pandemic. It can be done using a technology connecting internet by Android smartphone or a computer. Through this lecture is applying an online teaching learning process on the students’ speaking ability. The research objective is to determine the effect of online learning activity method on the university student on speaking at Ibrahimy University of Situbondo East Java. This research uses pre experimental research with one group pre-posttest design. The number of respondents was 07 persons who take an online learning activity. The data was taken using an application of kinemaster as pretest and posttest scores. The final data that can be conclude by comparing a mean score of the pretest and posttest. The average of pretest shows 49,3 and the average of posttest score shows 63,6.